Valorization and recycling of packaging belts and post-consumer PET bottles in the manufacture of sand concrete - Yasmina Biskri; Mohammed Benzerara; Laidi Babouri; Ouided Dehas; Redjem Belouettar (Fracture and Structural Integrity)
The valorization of local by-products in the manufacture of a new range of sand concrete and the improvement of their properties, will lead to seek an arrangement between performance and cost in order to achieve a resistant material. Waste recycling affects two very important affect namely the environmental impact and the economic impact. The main objective of our work is to contribute to optimize the formulation of sand concrete as part of the recovery of waste, which is harmful to the environment given its bulky and unattractive nature, it is waste plastic. Most PET bottles become waste after use, causing environmental problems. To solve this problem, a method for recycling PET bottles as fibers to strengthen concrete is proposed.